1999
DOI: 10.1074/jbc.274.51.36734
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of E-cadherin/Catenin Association by Tyrosine Phosphorylation

Abstract: Alteration of cadherin-mediated cell-cell adhesion is frequently associated to tyrosine phosphorylation of p120-and ␤-catenins. We have examined the role of this modification in these proteins in the control of ␤-catenin/E-cadherin binding using in vitro assays with recombinant proteins. Recombinant pp60 c-src efficiently phosphorylated both catenins in vitro, with stoichiometries of 1.5 and 2.0 mol of phosphate/mol of protein for ␤-catenin and p120-catenin, respectively. pp60 c-src phosphorylation had opposin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
429
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 547 publications
(445 citation statements)
references
References 35 publications
15
429
0
1
Order By: Relevance
“…Although we have not evaluated the phosphorylation status of p120, we found that the mean value of Src activity was higher in IDC with preserved p120 or E-CD expression than in those with reduced p120 or E-CD expression, thus implying that increased Src activity is not associated with a reduction in E-CD or p120. Our results are in accordance with previous experimental evidence that indicates that Src-induced p120 tyrosine phosphorylation increased its affinity for E-CD (Roura et al, 1999). As mentioned above, lobular tumors lack E-CD and b-catenin expression but accumulate p120 in the cytoplasm.…”
Section: Discussionsupporting
confidence: 82%
“…Although we have not evaluated the phosphorylation status of p120, we found that the mean value of Src activity was higher in IDC with preserved p120 or E-CD expression than in those with reduced p120 or E-CD expression, thus implying that increased Src activity is not associated with a reduction in E-CD or p120. Our results are in accordance with previous experimental evidence that indicates that Src-induced p120 tyrosine phosphorylation increased its affinity for E-CD (Roura et al, 1999). As mentioned above, lobular tumors lack E-CD and b-catenin expression but accumulate p120 in the cytoplasm.…”
Section: Discussionsupporting
confidence: 82%
“…The presence of Muc1 in MT-induced tumors promoted the association between c-Src and b-catenin. Tyrosine phosphorylation of b-catenin by c-Src at Y654 has been shown to disrupt the binding of b-catenin to E-cadherin (Roura et al, 1999). However, analysis of tumors from MT and MTK mice did not reveal a substantial change in the amount of b-catenin in association with Ecadherin, suggesting an alternate mechanism for weakening cadherin-dependent adhesions in PyV MT tumors.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study with MDCK kidney cells showed a gastrin-induced decrease in E-cadherin and b-catenin interaction (Bierkamp et al, 2002). Since tyrosine phosphorylation of b-catenin can modulate E-cadherin/b-catenin interaction Roura et al, 1999), it is possible that gastrin modulates b-catenin activity via modulating its tyrosine phosphorylation. In fact, studies by Hollande et al (2001), showed an increase in b-catenin tyrosine phosphorylation by G-17-Gly, although it is unclear whether a similar mechanism is activated by G-17 as well.…”
Section: Discussionmentioning
confidence: 99%